SaveMySkin: an internet-based self-help intervention for skin picking. Study protocol for a randomized pilot study - Gallinat, Christina; Moessner, Markus; Hänßle, Holger; Winkler, Julia K.; Backenstraß, Matthias; Bauer, Stephanie (Contemporary clinical trials communications, 2019)
Background - Skin picking disorder is an under-recognized and understudied mental disorder associated with severe psychological and medical consequences. Affected individuals barely receive adequate treatment, given the scarcity of expertise in healthcare professionals and the lack of evidence-based interventions. The present study seeks to evaluate an Internet-based self-help intervention for skin picking (“SaveMySkin”) within a pilot study. The intervention is based on cognitive-behavioral therapy (CBT) and provides comprehensive information materials and exercises. A daily supportive monitoring and psychological as well as dermatological counseling via Internet-chat provide additional support. The research questions focus on user attitudes, expectations and reservations, acceptance, adherences and user satisfaction as well as the feasibility of study procedures. Intervention effects will be estimated in order to plan a subsequent efficacy trial. - Methods - The pilot study will be conducted within a 2-arm randomized controlled trial design. A sample of N=100 participants will be recruited via Internet. Interested individuals will answer a short screening questionnaire and may register for the study, if they meet the inclusion criteria (age≥17, at least mild severity of skin picking). Following a baseline assessment, the intervention group may use SaveMySkin. The control group will have access to the intervention after completion of a waiting time of three months. - Discussion - The present trial will provide information on the feasibility and acceptability of an Internet-based intervention for individuals with skin picking. Furthermore, the results will be used to design a randomized controlled trial investigating the efficacy of the intervention. - Research registration number - German Register for Clinical Trials (DRKS): DRKS00015236;
Available online 10 December 2018
Gesehen am 27.04.2020